(3YjhH GdfaS heOGhGJgGs - (3CHh YHO GdQMef GdSdeis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdi Gddg Ydi eMeO hYdi Cdg CLejYf (B,(3HYO YjhH GdfaS djSJOd HgG Ydi eG hQGAgG s
(3BNQgG (B:s
(3ef YjhHgG TF HHYV gPg GdeOGhGJ bjSbW HPdc hYfOgG YjHkG ef YjhHgG hGddg JYGdi jhabfG GfJgi HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs